Effects of wheat gluten hydrolysate andits ultrafiltration fractions ondoughproperties and bread quality - Wang, Jinshui (Array, 2007)
Two fractions (50-K and permeate) from a proteolytic hydrolysate (degree of hydrolysis, DH=3.8 %) of wheat gluten were separated using ultrafiltration (UF) membrane with molecular mass cut-off of 50 kDa. The effects of the wheat gluten hydrolysate (WGH) and its UF fractions on the mixing behaviour and viscoelastic properties of wheat dough were presented. The WGH and its UF fractions modified the mixing properties of dough. The addition of these fractions improved the viscoelastic characteristics of wheat dough. A significant (p<0.05) effect of 50-K fraction on these characteristics of wheat dough was observed. After adding these fractions, the bread was considered acceptable by the sensory panel. Also, 50-K fraction resulted in significant (p<0.05) increase in the crumb firmness, while the bread made with wheat flour with WGH and permeate (P) fraction showed softer crumbs compared to that of wheat flour. Moreover, these fractions had anti-staling properties for bread during storage. Hence, the wheat gluten hydrolysate and its UF fractions are the products with promising potential in the baking products